2017
DOI: 10.1016/j.jacl.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Increase in acid sphingomyelinase level in human retinal endothelial cells and CD34+ circulating angiogenic cells isolated from diabetic individuals is associated with dysfunctional retinal vasculature and vascular repair process in diabetes

Abstract: Background Diabetic retinopathy (DR) is a microvascular disease that results from retinal vascular degeneration and defective repair due to diabetes induced endothelial progenitor dysfunction. Objective Understanding key molecular factors involved in vascular degeneration and repair is paramount for developing effective DR treatment strategies. We propose that diabetes-induced activation of acid sphingomyelinase (ASM) plays essential role in retinal endothelial and CD34+ circulating angiogenic cell (CAC) dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 61 publications
(72 reference statements)
0
34
0
Order By: Relevance
“…It has been well documented that increased prevalence of macrovascular and microvascular complications in type 2 diabetes mellitus (T2DM) is closely associated with impaired function of endothelial as well as endothelial progenitor cells (Fadini et al, 2005;Chen et al, 2009;Saboor et al, 2014;Yiu and Tse 2014;Kady et al, 2017). Endothelial progenitor cells (EPCs), recruited from the bone marrow and circulating in the peripheral blood, have the capability to differentiate into endothelial cells and seem to play a pivotal role for the repair of endothelium and to improve neovascularization (Schmidt-Lucke et al, 2005;Westerweel et al, 2013;Abplanalp et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been well documented that increased prevalence of macrovascular and microvascular complications in type 2 diabetes mellitus (T2DM) is closely associated with impaired function of endothelial as well as endothelial progenitor cells (Fadini et al, 2005;Chen et al, 2009;Saboor et al, 2014;Yiu and Tse 2014;Kady et al, 2017). Endothelial progenitor cells (EPCs), recruited from the bone marrow and circulating in the peripheral blood, have the capability to differentiate into endothelial cells and seem to play a pivotal role for the repair of endothelium and to improve neovascularization (Schmidt-Lucke et al, 2005;Westerweel et al, 2013;Abplanalp et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Additional causality and mechanistic studies are needed to more clearly define the relationship between CACs and diabetes in humans. Nevertheless, indications from prior human and animal studies are consistent with the idea that attenuated vascular repair due to low levels of pro-angiogenic cells, or dysfunctional pro-angiogenic cells promotes endothelial dysfunction and pathological outcomes such as retinopathy [ 29 ], neuropathy [ 11 , 35 ], and nephropathy [ 10 , 36 ].…”
Section: Discussionmentioning
confidence: 57%
“…Several prior animal [ 25 , 28 , 33 ] and human [ 24 , 26 , 27 , 29 ] studies have demonstrated an inverse relationship between CAC levels and incidence of diabetes. However, as these studies pre-selected the diabetic phenotype and used variable markers to identify CACs, it remains unclear which cell phenotype is most predictive of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DR depends on the entire retinal cell. The experimental manifestation of RD primarily owes to change in the retina [44]. Vision loss is mostly due to retinal dysfunction.…”
Section: Retinamentioning
confidence: 99%